Studi Kelayakan Pemilihan Supplier Perlengkapan Dan ATK Menggunakan Metode SAW (Simple Additive Weighting) - Hutagalung, Juniar (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Office Supplies and Stationery (ATK) are equipment that is often used in offices, companies and organizations, include cabinet filling, perforators, calculators, paper clips, staplers, numerators, guides, flashdisks, paper punches, pens and paper, paper shredder, computers, printers, facsimile machines, photocopiers, archive folders and cash registers, office furniture. Supplier is part of the supplier chain that influences the development of a company. Problems that are often experienced by PT. PLN Engineering such as late arrivals and lack of quality equipment and stationery from suppliers, therefore it needs to be re-ordered or returned to suppliers, so that time is wasted. Storage of data on procurement of equipment and stationery that are still conventional so that it is not effective and efficient in terms of time, cost and energy, let alone supplier selection which is still subjective. The purpose of this study makes it easier for competent parties to make decisions at PT. PLN Engineering in selecting the best supplier to be consistent in maintaining the determined criteria so as to minimize the risk and not disappoint the company. Incorrect supplier selection affects the quality and costs incurred in buying equipment and stationery from suppliers, how to overcome them requires a decision support system (SPK) that is able to accurately select the most suitable supplier. The method of Simple Additive Weighting (SAW) combined with fuzification is the right method for evaluating the best suppliers. The most important criteria are Price of Goods, Quality of Goods, Delivery Time, Location Distance, Goods Packaging, Accuracy of Goods, Flexibility, Track Record. The conclusion of the test results is the SAW method is able to show that the ranking of the best suppliers with the highest value of 0.89 is UD. Bintang Mulia.